MAGALHÃES, I. EU E TU: A CONSTITUIÇÃO DO SUJEITO NO DISCURSO MÉDICO. BRASÍLIA, THESAURUS, 2000, 181 PÁGS. - Santos, Edna Cristina S. (Cadernos de Linguagem e Sociedade, 2010)
MAGALHÃES, I. EU E TU: A CONSTITUIÇÃO DO SUJEITO NO DISCURSO MÉDICO. BRASÍLIA, THESAURUS, 2000, 181 PÁGS.